Thai Popular Songs for Children from 1939 to 1957 - Gavee, Jit (Journal of Cultural Approach, 2018)
A study of Thai popular songs for children during 1939-1957 is based on the musicology studies, using the method of the history and the qualitative analysis research. Data were obtained from printed material documents, electronic sources and interviewing the professionals who are composers, singers and music teachers. Analysis of data were completed by the method of western music theories. Results are as follow: Thai popular songs for children (1939 – 1957) can be divided in two sections. First, songs that have political influence and second, songs without any political influence, but they were used for children. During the period from 1939-1957, it was the period ruled by the prime minister, Field Marshal Plaek Phibunsongkhram. He ordered great changes concerning Thai culture and lifestyle of Thai people. Music was one of the key factor of changes. Many musical bands were under the control of Thai government, they were ordered to establish and compose new songs and play in public. Many songs from those bands appeared to be songs for children. In this period, there were many songs that showed specific need in improving the knowledge and understanding of the new politics, but also more songs were composed for improvement of ethics and public discipline of the young people. Those songs were played to teach young children in schools to teach and practice in the singing classes. Analysis studies showed various styles of children songs. All of them used western music form and melodies. New lyrics were composed along with the government ideas, but many were selected from old literature and plays as well as from the religious teaching document. Wordings were written in very fine Thai language with easy understanding. There were many form of music such as the binary, ternary, rondo and the 32 bars forms. Moreover, those children music and songs were also signified the historical evidences of the political dominances of which the government at the time had tried so hard to make the kingdom up to date and to be away from western colonization. Besides, the results also showed that Thailand had used western pop music as tools for modern national development of which those time western music studies in the country were not very popular like today. This might be a good reason to understand the progressive and well establishment of music schools in Thailand after the Second World War as well.